Human adipose-derived stem cells attenuate inflammatory bowel disease in IL-10 knockout mice. Issue 1 (February 2015) - Jung, Woo Yeun; Kang, Joo Hwan; Kim, Kyung Gon; Kim, Hee Snn; Jang, Byung Ik; Park, Yong Hoon; Song, In-Hwan
Highlights: Human adipose derived stem cells (hAMSCs) decreased gut inflammatory changes in IL-10 KO mouse. hAMSCs decreased Th1 related pro-inflammatory cytokines (IL-12, INF-γ, TNF-α) expression but had not changed Th2 related cytokine IL-4 in the colon of IL-10 KO mouse. The anti-inflammatory effect of hAMSCs in IL-10 KO mouse is expected to be mainly through suppression of Th1. Single injection of hAMSCs was delivered, the effect influenced chronic events associated with inflammatory changes in IL-10 KO mouse. Abstract: Inflammatory bowel disease (IBD) is a complex immunological disorder characterized by chronic inflammation caused mainly by unknown factors. The interleukin-10 knockout (IL-10 KO) mouse is a well-established murine model of IBD which develops spontaneous intestinal inflammation that resembles Crohn's disease. In the present study, human adipose-derived mesenchymal stem cells (hAMSCs) were administrated to IL-10 KO mice to evaluate the anti-inflammatory effects of hAMSCs that may attenuate the progress of or treat IBD. After IBD was induced by feeding the IL-10 KO mouse a 125–250 ppm piroxicam mixed diet for 1 week, 2 × 10 6 hAMSCs were injected into the peritoneum and the mice were switched to a normal diet. After 1 week, the mice were sacrificed and tissue samples were harvested. Tissue scores for inflammation and inflammation-related genes expression were determined. The hAMSC-treated group showed significantly reduced inflammatory changes in histological analysis. Reverse transcription-PCR analysis showed that RANTES, Toll-like receptor 9, and IL-4 expression levels were not significantly different between the groups while IL-12, INF-γ, and TNF-α levels were significantly decreased in the hAMSC treated group. hAMSC attenuated IBD in the IL-10 KO mice by suppressing inflammatory cytokine expression, was mediated by the type 1 helper T cell pathway. Even though only a single injection of hAMSCs was delivered, the effect influenced chronic events associated with inflammatory changes and demonstrated that hAMSCs are a powerful candidate for IBD therapy.